La mujer y su labor en el periodismo deportivo. Estudio de caso de la periodista deportiva María José Flores en las redes sociales Instagram y Twitter durante los meses de octubre, noviembre y diciembre de 2021. - Guamán Gonza, Viviana Nathaly (2023)
The present research project entitled "Women and their work in sports journalism. Case study of sports journalist María José Flores on social networks Instagram and Twitter during the months of October, November and December 2021" aims to recognize the work done by women in this area of communication, rescuing their achievements since the beginning of their career. The journalist Mará José Flores was taken as the axis of study since she is one of the pioneers in Ecuadorian sports journalism and has become a reference for new generations. Her work on social networks ranks her as one of the journalists with the most followers on Instagram and Twitter reaching approximately 500,000 followers.The mixed approach used facilitated the elaboration of observation sheets that group statistical data of the communicator María José Flores in social networks. Likewise, to collect testimonies from local, national and international journalists who rescue the achievements of women to date; With the help of the surveys, a new vision of the people’s approach to the new changes was achieved. The results showed that, thanks to the efforts made in recent years, journalists have opened up new opportunities because nowadays the female image in sports programs is indispensable to generate greater impact on the public. Keywords: cyberjournalism, communication and journalism, María José Flores, sports journalism, social networks.